Using technology to sell tactics to ratchet up results - London, Jonathan; Lucas, Martin 1977- (Apress, 2012)
"Shows salespeople and sales managers the most effective ways to leverage a variety of technologies to increase sales and gain more customers. Topics include making the most of cloud-based customer relationship management software, putting social media to the best use, presenting to customers worldwide through video conferencing, using advanced techniques like video "white papers" to differentiate your product or service, and gaining an information edge over competitors through alerts and other means"--Back cover
Includes index. - Print version record
Keywords: Target marketing; Consumer behavior; Selling -- Technological innovations; Sales management; economie; economics; bedrijfswetenschap; management science; Management studies, Business Administration, Organizational Science (General); Economics (General); Management, bedrijfskunde, organisatiekunde (algemeen); Economie (algemeen); Cibles (Marketing); Consommateurs; Comportement; Vente; Innovations; Ventes; Gestion; BUSINESS & ECONOMICS; E-Commerce; Internet Marketing; BUSINESS & ECONOMICS; Mail Order; BUSINESS & ECONOMICS; Marketing; Direct; BUSINESS & ECONOMICS; Marketing; Multilevel; BUSINESS & ECONOMICS; Marketing; Telemarketing; Selling; Technological innovations